2016
DOI: 10.1369/0022155416665577
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Minodronate in Mouse Femora Through Isotope Microscopy

Abstract: Minodronate is highlighted for its marked and sustained effects on osteoporotic bones. To determine the duration of minodronate's effects, we have assessed the localization of the drug in mouse bones through isotope microscopy, after labeling it with a stable nitrogen isotope ([(15)N]-minodronate). In addition, minodronate-treated bones were assessed by histochemistry and transmission electron microscopy (TEM). Eight-week-old male ICR mice received [(15)N]-minodronate (1 mg/kg) intravenously and were sacrifice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…Serial semi-thin sections of epoxy resin-embedded, undecalcified specimens of the middle region of tibial cortical bones were alternately mounted on silicon wafers and glass slides. Semi-thin sections mounted on silicon wafers were subjected to sputter coating with Au before observation under an isotope microscope 5154 at Isotope Imaging Laboratory, Creative Research Institute, Hokkaido University, Sapporo, Japan.…”
Section: Methodsmentioning
confidence: 99%
“…Serial semi-thin sections of epoxy resin-embedded, undecalcified specimens of the middle region of tibial cortical bones were alternately mounted on silicon wafers and glass slides. Semi-thin sections mounted on silicon wafers were subjected to sputter coating with Au before observation under an isotope microscope 5154 at Isotope Imaging Laboratory, Creative Research Institute, Hokkaido University, Sapporo, Japan.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have reported that radiolabeled BPs, including risedronate, alendronate, and minodronate, attach to the bone surface within 24 hours after i.v. injection . Osteoclasts secrete protons on the mineral surface to resorb bone tissues, resulting in the dissociation of BPs from the bone surface.…”
Section: Discussionmentioning
confidence: 99%
“…The exact localization of BPs within bones, as well as the ability of osteoclasts to take up BPs, has been well‐studied. Previous studies using radioactive isotopes reported that radiolabeled BPs localized to bone tissues and were taken up by osteoclasts within 24 hours after treatment in animal models . Another study using a fluorescent BP analogue also reported the localization of BPs on the bone surface and its cellular uptake by osteoclasts .…”
Section: Introductionmentioning
confidence: 96%
“…In mouse femora, minodronate accumulates in bone underneath osteoblasts rather than under osteoclasts and minodronate-coated bone matrix is resistant to osteoclastic resorption, suggesting bone-preserving effect by examining through isotope microscopy (Hongo et al 2016). In our study, case 8 was treated with minodronate for 4.1 years following with alendronate for 1.3 years and ES/BS in case 8 (3.19%) was not suppressed.…”
Section: Discussionmentioning
confidence: 99%